Wnt-β Catenin Signaling Pathway: A Major Player in the Injury Induced Fibrosis and Dysfunction of the External Anal Sphincter - M. Raj Rajasekaran (Nature Portfolio, 2017)
Abstract Wnt-β catenin is an important signaling pathway in the genesis of fibrosis in many organ systems. Our goal was to examine the role of Wnt pathway in the external anal sphincter (EAS) injury-related fibrosis and muscle dysfunction. New Zealand White female rabbits were subjected to surgical EAS myotomy and administered local injections of either a Wnt antagonist (sFRP-2; daily for 7 days) or saline. Anal canal pressure and EAS length-tension (L-T) were measured for 15 weeks after which the animals were sacrificed. Anal canal was harvested and processed for histochemical studies (Masson trichrome stain), molecular markers of fibrosis (collagen and transforming growth factor-β) and immunostaining for β catenin. Surgical myotomy of the EAS resulted in significant impairment in anal canal pressure and EAS muscle L-T function. Following myotomy, the EAS muscle was replaced with fibrous tissue. Immunostaining revealed β catenin activation and molecular studies revealed 1.5–2 fold increase in the levels of markers of fibrosis. Local injection of sFRP-2 attenuated the β catenin activation and fibrosis. EAS muscle content and function was significantly improved following sFRP-2 treatment. Our studies suggest that upregulation of Wnt signaling is an important molecular mechanism of injury related EAS muscle fibrosis and sphincter dysfunction.